Scaling up integrated management of childhood illness to national level: achievements and challenges in Peru - Huicho, Luis (2006)
This paper presents the first published report of a national-level effort to implement the integrated management of childhood illness (IMCI) strategy at scale. IMCI was introduced in Peru in late 1996, the early implementation phase started in 1997, with the expansion phase starting in 1998. Here we report on a retrospective evaluation designed to describe and analyze the process of taking IMCI to scale in Peru, conducted as one of five studies within the multicountry evaluation of IMCI effectiveness, cost and impact (MCE) coordinated by the World Health Organization. Trained surveyors visited each of Peru’s 34 districts, interviewed district health staff and reviewed district records. Findings show that IMCI was not institutionalized in Peru; it was implemented parallel to existing programmes to address acute respiratory infections and diarrhoea, sharing budget lines and management staff. The number of health workers trained in IMCI case management increased until 1999 and then decreased in 2000 and 2001, with overall coverage levels among doctors and nurses calculated to be 10,3%. Efforts to implement the community component of IMCI began with the training of community health workers in 2000, but expected synergies between health facility and community interventions were not done because districts where clinical training was most intense were not those where community IMCI training was strongest. We summarize the constraints to scaling up IMCI, and examine both the methodological and policy implications of the findings. Few monitoring data were available to document IMCI implementation in Peru, limiting the potential of retrospective evaluations to contribute to programme improvement. Even basic indicators recommended for national monitoring could not be calculated at either district or national levels. The findings document weaknesses in the policy and programme supports for IMCI that would cripple any intervention delivered through the health service delivery system. The Ministry of Health in Peru is now working to address these weaknesses; other countries working to achieve high and equitable coverage with essential child survival interventions can learn from their experience.